2000
DOI: 10.1016/s0895-7061(99)00196-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Mg++ concentrations in smooth and striated muscle cells in spontaneously hypertensive rats

Abstract: Decreased intracellular Mg++ concentrations seem to be involved in the pathogenesis of primary hypertension. Of special interest is the smooth muscle cell with its electrolyte metabolism in primary hypertension, but also heart muscle cells and their Mg++ concentrations are of growing interest. Therefore, in aortic smooth muscle cells and striated heart muscle cells (left ventricle) from 20 spontaneously hypertensive rats (SHR) of the Münster strain and 20 normotensive Wistar-Kyoto rats (WKY), the intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…A study by Hajek et al [14] showed an increase in PCr/Pi, PCr/bATP, PCr/Patp, and PDE/bATP ratios and a decrease in Pi/PDE, PCr/PME, and Pi/Patp ratios in the skeletal muscle of hypertensive individuals, and Sebekova et al [31] showed a lower ATP/Pi ratio and a higher PCr/ATP ratio in the skeletal muscle of insulinresistant patients with impaired kidney function. Lower phosphate content was found in the aortic smooth muscle cells in SHR [30].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A study by Hajek et al [14] showed an increase in PCr/Pi, PCr/bATP, PCr/Patp, and PDE/bATP ratios and a decrease in Pi/PDE, PCr/PME, and Pi/Patp ratios in the skeletal muscle of hypertensive individuals, and Sebekova et al [31] showed a lower ATP/Pi ratio and a higher PCr/ATP ratio in the skeletal muscle of insulinresistant patients with impaired kidney function. Lower phosphate content was found in the aortic smooth muscle cells in SHR [30].…”
Section: Discussionmentioning
confidence: 82%
“…The study by Jelicks et al [32] confirmed Mgi depletion in heart muscle cells, whereas the study by Kisters et al [30] did not demonstrate any difference. Conditions with reduced aortal distensibility, which represent a prerequisite for the development of hypertension, are also associated with a decrease in Mgi in skeletal muscle cells [33].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Many basic studies have shown that magnesium deficiency might be involved in the development of essential hypertension or borderline hypertension [14][15][16][17][18][19][20][21][22][23][24][25][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with exercise-and hyperventilation-induced angina or preeclampsia, intravenous infusion of Mg 2+ is effective [11,20,33]. A role for intracellular Mg 2+ in the pathogenesis of essential hypertension has been suggested in a recent study showing that [Mg 2+ ] i in vascular smooth muscle is significantly lower in spontaneously hypertensive rats, whereas that in skeletal myocytes does not differ between hypertensive and normal rats [10]. The mechanisms of the effect of Mg 2+ on vascular tone have been investigated widely [35,36], but little is known about the mechanism by which intracellular Mg 2+ regulates vascular tone.…”
Section: Introductionmentioning
confidence: 99%